The international federation for theory of machines and mechanisms - Erskine Crossley, F.R. (Journal of mechanisms, 1970)
This is a report on the founding of a new International Federation for the Theory of Machines and Mechanisms (IFToMM), which aims to work for increased international collaboration and understanding between scientists and engineers. It will sponsor an International Congress in TMM at four-year intervals. The Statutes which were adopted are reproduced here, and an attempt is made to define the field of TMM by listing its pertinent subjects. Die Internationale Federation für die Theorie von Maschinen und Mechanismen: Prof. F. R. Erskine Crossley. Dies ist ein Bericht über die Gründung einer neuen Internationalen Federation für die Theorie von Maschinen und Mechanismen (IFToMM), deren Ziel ist, die Arbeit zur Förderung der internationalen Zusammenarbeit und Verständigung zwischen Wissenschaftlern und Ingenieuren. IFToMM wird die Einrichtung eines Internationalen Kongresses für TMM in 4-jahrigen Intervallen unterstützen. Die angenommenen Statue werden unten reproduziert und ein Versuch wird gemacht den Wirkungsbereich von TMM zu bestimmen durch angemessene Verzeichnung der Fächer. ИнTepнaциoнaлянaя фeдepaция пo Teopии мaШин и мexaHизMoB: Пpoф. Ф. P. Epcкин КpoccлeЙ. HacтoяШaя cтaтя являeтcя oтчeтoм пo ocнoвaнию нoвoй интepнaциoнaлвнoй фeдepaции пo тeopии мaШин и мexaнизмoв (ИфToMM), цeлШю кoтopoй являeтcя paбoтa и yвeличeнию мeждyнapoдoй coвмecтнoй paбoты и взaимoпoнимaния мeждy yчeными и инжeнepaми. ИфToMM бyдeт пoддepживaть ycтpoйcтвo интepнaциoнaльныx кoнгpeccoв пo TMM в чeтыpexлeтниx пpoмéжyткax. Пpинятыe cтaтyты peпpoдyциpyютcя нижe и дeлaeтcя пoпыткa oгpaничитш пoлe дeятeлШнocти TMM пepeчиcлeниeм cooтвeтcвeнныx пpeдмeтoв.